The Impact of Emojis in Online Customer Support Services : A study about the brand emoji use and the reciprocity in the use of emoji between customers and e-retailers - Santos, Raquel Lopes Tonico dos (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM